2017
DOI: 10.4103/2303-9027.209869
|View full text |Cite
|
Sign up to set email alerts
|

Use of partially covered and uncovered metallic prosthesis for endoscopic ultrasound-guided hepaticogastrostomy: Results of a retrospective monocentric study

Abstract: Background and Objectives:Endoscopic ultrasound-guided hepaticogastrostomy (EUS-HGS) represents an option to treat obstructive jaundice when endoscopic retrograde cholangiopancreatography (ERCP) fails. The success rate of this procedure has been shown to be very high. Up to now, plastic and self-expandable metallic stents (SEMSs) have been employed, each of them presenting some limitations. The aims of this study were to evaluate the technical and functional success rates of EUS-HGS using a dedicated biliary S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
19
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 52 publications
(21 citation statements)
references
References 34 publications
2
19
0
Order By: Relevance
“…Outside of the United States, specially designed stents for the purpose of EUS-HE are commercially available, such as Giobor stent (Taewoong Medical, Gyeonggi-do, South Korea) and Zeo Stent (ZEON Medical, Tokyo, Japan). Our study found a technical success rate for EUS-HE of 88.3 %, which is comparable to prior studies using these dedicated stents 14 15 .…”
Section: Discussionsupporting
confidence: 87%
“…Outside of the United States, specially designed stents for the purpose of EUS-HE are commercially available, such as Giobor stent (Taewoong Medical, Gyeonggi-do, South Korea) and Zeo Stent (ZEON Medical, Tokyo, Japan). Our study found a technical success rate for EUS-HE of 88.3 %, which is comparable to prior studies using these dedicated stents 14 15 .…”
Section: Discussionsupporting
confidence: 87%
“…Until recently, these limitations were overcome by inserting an FCSEMS into a UCSEMS with the drawback of multiple manipulations and costs. [143334] These shortcomings led to the development of novel “hybrid” metal stents. [1434] Hybrid stents are PC SEMS, which are fully covered at the distal portion to prevent bile leakage, and UC at the proximal portion to prevent biliary side branch obstruction.…”
Section: Available Designs Of Eus-specific Stents and Their Indicationsmentioning
confidence: 99%
“…[143334] These shortcomings led to the development of novel “hybrid” metal stents. [1434] Hybrid stents are PC SEMS, which are fully covered at the distal portion to prevent bile leakage, and UC at the proximal portion to prevent biliary side branch obstruction. Furthermore, they have anti-migratory mechanisms (flaps or flares) and present sufficient stent length to prevent proximal migration into the peritoneum.…”
Section: Available Designs Of Eus-specific Stents and Their Indicationsmentioning
confidence: 99%
See 2 more Smart Citations